Nerve Growth Factor Is Responsible for Exercise-Induced Recovery of Septohippocampal Cholinergic Structure and Function - Hall, Joseph M.; Gomez-Pinilla, Fernando; Savage, Lisa M. (Frontiers in Neuroscience, 2018)
Exercise has been shown to improve or rescue cognitive functioning in both humans and rodents, and the augmented actions of neurotrophins within the hippocampus and associated regions play a significant role in the improved neural plasticity. The septohippocampal circuit is modified by exercise. Beyond an enhancement of spatial working memory and a rescue of hippocampal activity-dependent acetylcholine (ACh) efflux, the re-emergence of the cholinergic/nestin neuronal phenotype within the medial septum/diagonal band (MS/dB) is observed following exercise (Hall and Savage, 2016). To determine which neurotrophin, brain-derived neurotrophic factor (BDNF) or nerve growth factor (NGF), is critical for exercise-induced cholinergic improvements, control and amnestic rats had either NGF or BDNF sequestered by TrkA-IgG or TrkB-IgG coated microbeads placed within the dorsal hippocampus. Hippocampal ACh release within the hippocampus during spontaneous alternation was measured and MS/dB cholinergic neuronal phenotypes were assessed. Sequestering NGF, but not BDNF, abolished the exercise-induced recovery of spatial working memory and ACh efflux. Furthermore, the re-emergence of the cholinergic/nestin neuronal phenotype within the MS/dB following exercise was also selectively dependent on the actions of NGF. Thus, exercise-induced enhancement of NGF within the septohippocampal pathway represents a key avenue for aiding failing septo-hippocampal functioning and therefore has significant potential for the recovery of memory and cognition in several neurological disorders.